Stability analysis of photovoltaic interface converter using the dynamic model of photovoltaic cell. (November 2022) - Liu, He; Qu, Lu; Tong, Qiang
Abstract: In a photovoltaic (PV) power generation system, a power interface converter is required to manage the power flow between the PV cells, battery, or load. Conventionally, while designing loop controller parameters, an ideal current or voltage source with a fixed resistor is adopted to simulate the panel characteristics However, significant differences exist between the actual performance of real panels and that of the above two alternatives; additionally, controllers designed with a definite equivalent model may lack a response. In this study, the small-signal model of a power interface converter, comprising the dynamic characteristics of PV cells, was developed for different operating modes to solve the aforementioned problems. On this basis, frequency response comparisons of the power stage transfer function were used to analyze the stability margin with parameter variations. Consequently, it was concluded that the dynamic capacitance and equivalent output resistance of the PV cells could not be ignored. Therefore, a controller design approach for the worst case was developed. The mathematical analysis was verified based on a prototype simulation and a thorough investigation of the waveforms.